The Use of â€œMonumen Perjuangan Rakyat Jawa Baratâ€ Museum Collection as Social Studies Learning Resources - Zainab, Linda (Universitas Pendidikan Indonesia, 2019)
This research is arranged by seeing the reality in school that some of the resources used by teachers are limited with no any various resources to learn social studies subject in junior high school. This research is also done to describe the relevance of the museum that can be benefited as social studies resources. The approachment used for this research is qualitative and descriptive method implemented in Museum Monumen Perjuangan Rakyat Jawa Barat. Technique of collecting data used for this research is observation, interview, and documentation. Based on the findings of the research, the museum collection in Museum Monumen Perjuangan Rakyat Jawa Barat is relevance with social studies resources for junior high school. As for basic competence of social studies subject which in appropriate with the museum collection is the material on KD (Basic Competence) 3.4 and KD 4.4 class VII, VIII, and IX of junior high school. The values contained in the museum collection are value of struggle, nasionalism, braveness, caring, mutual cooperation, and value of patriotism. The use of this museum is for learning process of social studies which is using Project Based Learning model, for instance, the making of vlog is given to students to tell their observation result from the museum also the teacher could ask students to do self-reflection after visiting the museum.